Separable arrowhead polymer microneedles - Zhang, Xuyang (2015)
Currently, majority of biopharmaceutical medicine are delivered exclusively through syringe and hypodermic needle system. But those methods have significant drawbacks such as pain, bleeding, production of bio-hazardous shape waste etc. Ideally, a transdermal drug delivery system should have features of (a) safe injection; (b) a wide range of molecular weight of therapeutics chemical compounds delivery; (c) controlled drug release kinetics; (d) cost-effectiveness; and (e) user-friendly. With all those characteristics, current microneedle system has addressed the issue of syringe and hypodermic needle system, but further research and innovation are needed to optimize the microneedle system. One of the current advances of microneedle fabrication is separable arrowhead microneedles with the feature of sharp micro-size polymer tips mounted on unpointed metal shafts. On insertion of microneedles into the skin, the drug encapsulated arrowhead polymer tips separate from their metal shafts. These sharp tips keep embedded under stratum corneous for consequent tip dissolution and then drug release, while metal shafts can be disposed. [4] But the fabrication process of metal shaft is complicated and expensive. Thus, this project used polymer PEGDA (Poly(ethylene)-glycol-diacrylate) shaft to replace the metal shaft to gain low-cost mass-production fabrication. Moreover, in order to elongate the storage lifetime of polymer microneedle especially in the high humidity environment, the selection of microneedle tip material was featured with low water absorption. PVP (Polyvinylpyrrolidone) incorporated with 2-Hydroxypropyl-Beta- Cyclodextrin (2- HP-β-CD) were chosen to form PVP-CD complex as the tip material.